2019
DOI: 10.18203/2320-6012.ijrms20194622
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-bacteriological profile of spontaneous bacterial peritonitis in cirrhosis of liver with ascites

Abstract: Background:A good and an effective empirical treatment of SBP is not possible unless bacteriological spectrum and their antibiogram is clear. This becomes more important in country like India due to high antibiotic resistance. Authors aim was to assess the prevalence of SBP, clinical and microbiological profile of its variants, in patients with cirrhosis seeking care at a tertiary care teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
0
1
Order By: Relevance
“…35.5% in another study in Assuit [36] and 41.7% in Tanta [37]. The prevalence of SBP in the current study was higher than that reported in a global study on 1,302 patients from Asia, Europe and America which was 27% [10] and that reported in two different Indian studies as it was 38.09% [38] and 16.12% [39]. This difference may be attributed to the difference in samples' size, the mean age and the type of studied patients (whether inpatients or outpatients, symptomatic or asymptomatic), the wide use of PPI in the present study (73%) which may be a risk factor for SBP [40] [42].…”
Section: Discussioncontrasting
confidence: 65%
“…35.5% in another study in Assuit [36] and 41.7% in Tanta [37]. The prevalence of SBP in the current study was higher than that reported in a global study on 1,302 patients from Asia, Europe and America which was 27% [10] and that reported in two different Indian studies as it was 38.09% [38] and 16.12% [39]. This difference may be attributed to the difference in samples' size, the mean age and the type of studied patients (whether inpatients or outpatients, symptomatic or asymptomatic), the wide use of PPI in the present study (73%) which may be a risk factor for SBP [40] [42].…”
Section: Discussioncontrasting
confidence: 65%
“…Diagnostic paracentesis should always be performed for all cases of ascites, irrespective of cause [15]. A microbiological study by means of ascitic fluid culture and antibiotic susceptibility testing should also be performed to find out the causative organism and its sensitivity pattern in cases of infected ascites and thereby improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%